Prevalence of Chronic Rhinosinusitis in ENT Departement RSUP Dr. Mohammad Hoesin Palembang - Challis Malika Ravantara; Yoan Levia Magdi; Bahrun Indawan Kasim (Sriwijaya Journal of Medicine, 2020)
Introduction: Prevalence of Chronic Rhinosinusitis in ENT Department RSUP Dr. Mohammad Hoesin Palembang Period 2016-2018. Chronic rhinosinusitis (CRS) is an inflammation involving the nose and paranasal sinuses where the patient has two or more major symptoms or one major symptom with two minor symptoms for ≥12 weeks. The prevalence of CRS throughout the world population is around 10-12%. The prevalence of CRS in Indonesia is uncertain. A research has been conducted on the prevalence of CRS in RSUP Dr. Mohammad Hoesin Palembang in 2015, therefore this study aims to find out more about the prevalence of CRS in the ENT Department of Dr. Mohammad Hoesin Palembang General Hospital in the period 2016-2018 and its distribution based on age, sex, major symptoms, minor symptoms, and the number of sinuses involved. Methods: This research was an observational descriptive survey with cross-sectional design. This study used medical records of CRS patients undergoing surgery in the Rhinology Division of the ENT Department RSUP Dr. Mohammad Hoesin Palembang period 2016-2018. Sampling was done by consecutive sampling method. The amount of samples in this research is 99 cases. The result of this research is presented in table and narration form. The prevalence of CRS was 33.55%. CRS is most commonly found by the age group 46-53 years (21.2%), male sex (65.7%) with a ratio between men and women 1.9: 1. The most common major symptom was nasal congestion (100%) and the most common minor symptom was headache (62.6%). The most number of sinuses involved based on the paranasal sinus CT scan results was multiple sinusitis (52.5%).